Speech Melody Properties in English, Czech and Czech English: Reference and Interference - Volín, Jan; Poesová, Kristýna; Weingartová, Lenka (Research in Language, 2015)
Two major objectives were set for the present study: to provide reference data for the description of Czech and English F0 contours, and to investigate the limits of the ‘interference hypothesis’ on Czech English data. Altogether, the production of 40 speakers in 2392 breath-group F0 contours was analyzed. The speech of 32 professional speakers of English and Czech provides reference values for various acoustic correlates of pitch level, pitch span and downtrend gradient. These values were subsequently used as a benchmark for a confirmation of the interference hypothesis through comparison with a further sample of 8 non-professional speakers of English and Czech-accented English. The native English speakers of both genders produced significantly higher pitch level indicators, wider pitch span and a steeper downtrend gradient than the reference native speakers of Czech. Although the pitch level of the Czech-accented material lies in between the two reference groups, the pitch span of this group is the narrowest, which indicates that factors of foreign-accentedness other than simply interference are in effect.